The investment policy and regional development of Serbia in the transition period - Aničić Jugoslav; Laketa Marko; Vukotić Svetlana (Zbornik Radova: Geografski institut "Jovan Cvijić", 2011)
Our country can compensate the lagging in the economic development in relation to the EU countries as well as to the countries of the region only by increasing the economy's competitiveness, depending to a great extent on the possibilities of the economic entities investment in improving the attributes of the existing and development of new products and services, as well as on introducing modern technology and technological procedures. The transition program conducted by former socialist countries was highly based on foreign direct investments (FDI) enabling these countries the successful inclusion into global flows of international production and overall economy. In this paper the possibilities and sources of our economy investing will be analyzed and the influence on enhancement of the overall and regional competitiveness of the companies as a necessary condition for increasing the export and the overall economic development of the country.